Effect of Api-Bioxal® and ApiHerb® Treatments against Nosema ceranae Infection in Apis mellifera Investigated by Two qPCR Methods - Giovanni Cilia; Claudia Garrido; Martina Bonetto; Donato Tesoriero; Antonio Nanetti (Veterinary Sciences, 2020)
Nosema ceranae is a worldwide distributed midgut parasite of western honey bees, leading to dwindling colonies and their collapse. As a treatment, only fumagillin is available, causing issues like resistance and hampered bee physiology. This study aimed to evaluate ApiHerb® and Api-Bioxal® as treatments against N. ceranae. The efficacy was tested using two qPCR methods based on the 16S rRNA and Hsp70 genes. In addition, these methods were compared for their aptitude for the quantification of the infection. For this, 19 colonies were selected based on the presence of N. ceranae infections. The colonies were divided into three groups: treated with ApiHerb, Api-Bioxal with previous queen caging and an untreated control. All colonies were sampled pre- and post-treatment. The bees were analyzed individually and in duplicate with both qPCR methods. All bees in the pre-treatment tested positive for N. ceranae. Both treatments reduced the abundance of N. ceranae, but ApiHerb also decreased the prevalence of infected bees. Analysis with the 16S rRNA method resulted in several orders of magnitude more copies than analysis with the Hsp70 method. We conclude that both products are suitable candidates for N. ceranae treatment. From our analysis, the qPCR method based on the Hsp70 gene results as more apt for the exact quantification of N. ceranae as is needed for the development of veterinary medicinal products.